Analysis of Digital Marketing Implementation, 7P Marketing Mix Strategy, and Product Innovation to Increase Sales Volume through Competitive Advantage as an Intervening Variable in Sidoarjo Regency MSMEs - Arista, Sintha Wahyu; Hermawan, Sigit; Sukmono, Rita Ambarwati (Jurnal Manajemen (Edisi Elektronik), 2025)
The purpose of this study is to test and determine the effect of digi-tal marketing implementation, the use of marketing mix, and the product innovation on increasing sales volume through gaining competitive advantage. This study focuses on the population of MSME participants in the culinary industry that have been regis-tered in the data of the Sidoarjo Regency Cooperative and MSME Service in Sidoarjo Regency. The method in this study uses a quantitative method. Data collection uses a survey or question-naire. Data analysis is a quantitative or statistical process that involves evaluating established hypotheses. Data sources used in this study include primary and secondary sources. The results ob-tained in this study are: 1) digital marketing, marketing mix strat-egies, and product innovation have a partial positive effect on in-creasing sales volume; 2) digital marketing, marketing mix strate-gies, and product innovation have a partial positive effect on com-petitive advantage; 3) competitive advantage has a partial positive effect on increasing sales volume; 4) digital marketing has a sig-nificant positive effect on sales volume through competitive ad-vantage; 5) marketing mix strategies have a significant positive effect on sales volume through competitive advantage; 6) product innovation has a significant positive effect on sales volume through competitive advantage. This study underlines the im-portance of a holistic approach in improving MSME performance, which combines digital marketing, intellectual capital, product innovation and competitive advantage synergistically. MSME players are expected to be able to develop strategies that integrate these elements to achieve better prosperity and competitiveness in the market.